Pengaruh Ukuran Perusahaan, Profitabilitas dan Kantor Akuntan Publik Terhadap Audit Delay (Studi Empiris Pada Perusahaan Manufaktur Sektor Aneka Industri Periode 2019-2022) - Anand, Syakira Rezky; ., Indupurnahayu; Riani, Desmy (CV. ITTC INDONESIA, 2024)
This research aims to determine the effect of company size, probability and size of the public accounting firm on audit delay in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange for the 2019-2022 period. Quantitative research methods and descriptive statistical analysis with a population of 55 companies, observation period is 4 years, with a sample of 9 companies with 36 financial reports (according to the criteria). Data analysis used E-Views 12 software. The results showed that company size, profitability and the size of the public accounting firm silmutaneously influenced audit delay. Partially, the company size variable has a significant negative effect on audit delay. Partially, the company size variable has a significant negative effect on audit delay, and the profitability variable. The size of the public accounting firm, does not have a significant effect on audit dela